2020
DOI: 10.1177/0265407520910784
|View full text |Cite
|
Sign up to set email alerts
|

Children’s friendship quality trajectories from middle childhood to early adolescence and prediction from sex

Abstract: We investigated the development of children’s self-reported positive (Companionship and Recreation, Validation and Caring, Help and Guidance, Intimate Disclosure, and Conflict Resolution) and negative (Conflict and Betrayal) friendship quality from the third to sixth grades using The National Institute of Child Health and Development (NICHD) Study of Early Child Care and Youth Development data (NICHD SECCYD; n = 1,364; M age = 9.03 years; 51.70% boys at recruitment). Consistent with expectations, growth models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 18 publications
(29 reference statements)
2
12
0
3
Order By: Relevance
“…Hanya saja, signifikansi klinis dari temuan ini perlu ditelaah secara hati-hati, mengingat studi ini Furthermore, the results of this study also confirmed the results of a number of previous pieces of research, which showed that female adolescents have higher positive friendship quality than male adolescents (Biggs et al, 2012;Kouwenberg et al, 2013;Xu et al, 2020). This difference may be caused by differences in the features of friendship between those of males and females.…”
Section: Diskusisupporting
confidence: 84%
See 3 more Smart Citations
“…Hanya saja, signifikansi klinis dari temuan ini perlu ditelaah secara hati-hati, mengingat studi ini Furthermore, the results of this study also confirmed the results of a number of previous pieces of research, which showed that female adolescents have higher positive friendship quality than male adolescents (Biggs et al, 2012;Kouwenberg et al, 2013;Xu et al, 2020). This difference may be caused by differences in the features of friendship between those of males and females.…”
Section: Diskusisupporting
confidence: 84%
“…This difference may be caused by differences in the features of friendship between those of males and females. Female adolescent friendships are normally marked by the presence of self-disclosure, support, closeness, and togetherness (Kuttler et al, 1999;; while friendship amongst male adolescents is marked by higher levels of autonomy and low levels of selfdisclosure (Cross & Madson, 1997), causing the friendships of male adolescents to take longer to exit and recover from negative friendship, compared to those of female adolescents (Xu et al, 2020).…”
Section: Diskusimentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to age, research has shown that friendship quality increases from middle childhood to adolescence and throughout adolescence (Sánchez-Queija & Oliva, 2015;Way & Greene, 2006;Xu, Eggum-Wilkens, & Bradley, 2020): loyalty, intimacy and self-disclosure seem to increase during adolescence (Buhrmester, 1990;Rubin et al, 2008;Weiss & Smith, 2002). Furthermore, Rubin et al (2008) reported that friendships at age 7 to 8 focus on convenience and rewards/costs; whereas friendships at age 10 to 11 focus on loyalty and sharing the same values.…”
Section: The Role Of Gender and Age In The Relationship Between Friendship Quality And Nssimentioning
confidence: 99%